2020
DOI: 10.1146/annurev-ento-011019-025055
|View full text |Cite
|
Sign up to set email alerts
|

Non-Bee Insects as Visitors and Pollinators of Crops: Biology, Ecology, and Management

Abstract: Insects other than bees (i.e., non-bees) have been acknowledged as important crop pollinators, but our understanding of which crop plants they visit and how effective they are as crop pollinators is limited. To compare visitation and efficiency of crop-pollinating bees and non-bees at a global scale, we review the literature published from 1950 to 2018 concerning the visitors and pollinators of 105 global food crops that are known to benefit from animal pollinators. Of the 105 animal-pollinated crops, a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
185
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(194 citation statements)
references
References 94 publications
5
185
0
4
Order By: Relevance
“…Family Nymphalidae contains relatively lower pollinating species (Figure 2), as most members of this family feed on decomposition liquid [8]. Although previous publications partly analysed the role of butterflies in pollination (mainly for long-tongued species in family Papilionidae, Pieridae, and Nymphalidae) [3,9], the pollen transportation efficiency of each butterfly family is still poorly understood. Even though the present research did not perform analyses of pollen transportation efficiency, the 10-year cumulative field observation by the authors of feeding-oriented flower visiting (not random perching) could provide some clues.…”
Section: Potential Benefits and Conservation Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Family Nymphalidae contains relatively lower pollinating species (Figure 2), as most members of this family feed on decomposition liquid [8]. Although previous publications partly analysed the role of butterflies in pollination (mainly for long-tongued species in family Papilionidae, Pieridae, and Nymphalidae) [3,9], the pollen transportation efficiency of each butterfly family is still poorly understood. Even though the present research did not perform analyses of pollen transportation efficiency, the 10-year cumulative field observation by the authors of feeding-oriented flower visiting (not random perching) could provide some clues.…”
Section: Potential Benefits and Conservation Implicationsmentioning
confidence: 99%
“…Although the service value of pollinating butterflies is still less understood, some studies already confirmed their role in increasing yield and quality of agricultural products [98]. Such benefits are more evident in fruit horticulture and some cash crops than food crops, as many food crops belong to family Poaceae with relatively limited attracting ability to lepidopterous pollinators [3]. In comparison, fruit trees and cash crops with more developed and colourful flowers are more frequently visited by butterflies [3], and thus benefited from their diversity.…”
Section: Potential Benefits and Conservation Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their numerical dominance, social bees are not the only insect pollinators, nor are they always the most efficient or important pollinators for all crop plants and their wild relatives (rev. by Rader et al 2016Rader et al , 2019. Another consequence of increased global awareness of pollinator vulnerability has been a growing appreciation for the diversity and abundance of flower-visiting flies (Diptera) and their potential as alternative pollinators (Mitra and Banerjee 2007;Orford et al 2015;Ssymank et al 2008).…”
Section: Introductionmentioning
confidence: 99%